Pengelolaan Risiko Privasi Data Siswa : Kerangka Kerja Administrasi Pendidikan Digital Di SDN 08 Cupak - Nadila, Nadila (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This research is aimed at analyzing Data Privacy Risk Management within educational institutions in the digital era. The increasing adoption of technology in educational administration, such as e-report cards and academic information systems, inherently increases the risk of security crises and student data breaches. This study is expected to formulate an integrated risk management model that aligns with the principles of accountable educational administration governance. The method used is descriptive qualitative, employing a systematic literature review approach on relevant risk management frameworks and data protection regulations. The data will be analyzed to identify critical stages ranging from data asset identification and vulnerability analysis, to designing appropriate control mechanisms and risk mitigation strategies. The identification results are expected to provide a conceptual guide for educational administrators in maintaining and building strong data security pillars to promote a secure digital transformation.